Beta variant COVID-19 protein booster vaccine elicits durable cross-neutralization against SARS-CoV-2 variants in non-human primates - Vincent Pavot; Catherine Berry; Michael Kishko; Natalie G. Anosova; Lu Li; Tim Tibbitts; Dean Huang; Alice Raillard; Sylviane Gautheron; Cindy Gutzeit; Marguerite Koutsoukos; Roman M. Chicz; et al. (Nature Communications, 2023)
Waning protective efficacy of mRNA-based booster vaccinations has been observed against newly emerging SARS-CoV-2 variants of concern. In this work, Pavot et al. formulate a monovalent Beta vaccine and demonstrate durable cross-neutralising antibody responses in non-human primates, against a spectrum of variants.